THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND LEARNING EFFECTIVENESS ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION AS A MEDIATING VARIABLE - Warsita, Atep; Maliki, Budi Ilham; Komarudin, Mamay (STKIP Citra Bakti, 2026)
Teacher performance constitutes a primary determinant of educational quality; however, variations across schools indicate the need to identify the most influential organizational and instructional factors. This study aims to analyze the influence of transformational leadership and learning effectiveness on teacher performance, with work motivation serving as a mediating variable, at public senior high schools under Branch Office XI in Garut Regency. A quantitative approach with a correlational–explanatory design was employed. The sample consisted of 93 teachers selected through proportionate stratified random sampling. Data were collected using structured questionnaires and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that learning effectiveness has a positive and significant effect on teacher performance (? = 0.726; p < 0.001) and work motivation (? = 0.689; p < 0.001). Work motivation significantly affects teacher performance (? = 0.195; p = 0.010) and partially mediates the relationship between learning effectiveness and teacher performance. In contrast, transformational leadership does not exert a significant effect on either work motivation or teacher performance within the sampled context. The model demonstrates strong predictive power for teacher performance (R² = 0.834). These results suggest that strengthening effective instructional practices and motivation-enhancement strategies plays a more decisive role than leadership style alone in improving teacher performance. The study is limited by its cross-sectional design, reliance on self-reported data, and focus on a single regional context; therefore, generalization should be undertaken with caution.